Capacity of two Staphylococcus aureus strains with different adaptation genotypes to persist and induce damage in bovine mammary epithelial cells and to activate macrophages - Sacco, Sofía Clara; Velázquez, Natalia S.; Renna, María Sol; Beccaria, Camila; Baravalle, Celina; Pereyra, Elizabet Amanda Lorena; Monecke, Stefan; Calvinho, Luis Fernando; Dallard, Bibiana Elisabet (Elsevier, 2020)
The aim of this study was to evaluate and compare the ability to adhere/internalize, persist, and induce damage in mammary epithelial cells (MAC-T) of two Staphylococcus aureus strains with different adaptation genotypes (low and high) to the bovine mammary gland (MG). Also, the phagocytic and bactericidal capacity induced after the interaction between macrophages, isolated from mammary secretion, of both S. aureus strains was evaluated. Two isolates (designated 806 and 5011) from bovine intramammary infection (IMI) harboring genes involved in adherence and biofilm production, belonging to different capsular polysaccharide (CP) type, accessory gene regulator (agr) group, pulsotype (PT) and sequence type/clonal complex (ST/CC). Strains 806 and 5011 were associated with low (nonpersistent-NP) and high (persistent-P) adaptation to the MG, respectively. Strain 5011 (P), agr group I, cap8 positive and strong biofilm producer showed higher capacity to adhere/internalize in MAC-T compared with strain 806 (NP), characterized as agr group II, cap5 positive and weak biofilm producer. Strain 5011(P) could be recovered from MAC-T lysates up to 72 h pi; while strain 806 (NP) could be recovered only at 4 h pi. Strain 5011 (P) showed greater capacity to induce apoptosis compared with strain 806 (NP) at 4, 24 and 48 h pi. Macrophages infected with strain 5011 (P) showed a greater phagocytic capacity and higher percentage of intracellular reactive oxygen species (ROS) production than strain 806 (NP). No viable bacteria were isolated from macrophages lysates stimulated with any of the S. aureus strains at 2, 4, 8 and 24 h pi. The knowledge of the molecular profile of the S. aureus strains causing bovine mastitis in a herd could become a tool to expose the most prevalent virulence gene patterns and advance in the elucidation of the pathogenesis of chronic mastitis.